2017
DOI: 10.3892/etm.2017.4119
|View full text |Cite
|
Sign up to set email alerts
|

Association of white blood cell counts with left ventricular mass index in hypertensive patients undergoing anti-hypertensive drug therapy

Abstract: Although studies using animal models have demonstrated that nonhemodynamic factors, including inflammatory cells and cytokines, contribute to left ventricular hypertrophy (LVH), there is little clinical data to confirm this association. Therefore in the present study, levels of circulating specific types of leukocyte were measured to determine the association between white blood cells and left ventricular mass index (LVMI) in hypertensive patients undergoing anti-hypertensive drug therapy. A total of 144 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…obesity, body size, insulin, and the renin-angiotensin system contribute to LVH development [18]. Also, nonhemodynamic factors, including transforming growth factor β1, tumor necrosis factor-alpha (TNF-a), and cytokines plays an important role in LV remodelling [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…obesity, body size, insulin, and the renin-angiotensin system contribute to LVH development [18]. Also, nonhemodynamic factors, including transforming growth factor β1, tumor necrosis factor-alpha (TNF-a), and cytokines plays an important role in LV remodelling [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have investigated the relationship between NLR, HT, and LVMI. Shi, et al [20] demonstrated that a strong correlation between WBC counts (particularly neutrophil counts) and LVMI in hypertensive patients currently taking anti-hypertensive medication. Our findings are consistent with this study results, and we showed that NLR was positively correlated whit LVH in CH and EH groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the NHANES I Epidemiological Follow-up Study (NHEFS) reported an association between higher WBC count and increased incidence of hypertension in white men, and possibly in older white and black women [35]. In a study conducted by Shi et al [36], it was found that certain types of circulating leukocytes in hypertensive patients using antihypertensive medications might be linked to left ventricular hypertrophy (LVH).…”
Section: White Blood Cellsmentioning
confidence: 99%